Commons and refiguration of education - Pechtelidis, Yannis (The Greek Review of Social Research, 2020)
This text introduces the emerging paradigm of the ‘commons’ as an alternative value and action system in the field of formal education. The main aim is to critically discuss the possibilities of refiguring the institutional formal education, both at the level of educational activity and governing or administration, following the values of equality, autonomy, community, participation, cooperation and sharing. At the heart of the study lies the ‘commoning’ process as an alternative educational and micro-political process that emerges in the cracks of the formal education system by creating practices that challenge the dominant discourse for education and society. Also, the similarities and differences of educational commons from other alternative educational narratives are critically investigated.